Reaffirming the Value of the Autopsy: 10-Year Review of Acute Myocardial Infarction Diagnosed at Autopsy. (21st September 2018) - Sathirareuangchai, Sakda; Shimizu, David
Abstract: Introduction: Autopsy remains a unique procedure performed by pathologists, providing definitive diagnoses to clinicians and patients' families. Performance of autopsy and correlation with the premortem clinical diagnoses is also an important component of health care quality management. Acute myocardial infarction (MI) detected at autopsy is one of the most common diagnoses that exhibits discordance between the pathologic and clinical impressions. We conducted this study to determine characteristic features of acute MI diagnosed at autopsy and correlate the clinical and pathologic diagnoses in an effort to establish the incidence of discrepancy. Methods: We conducted a 10-year retrospective review of autopsy cases at the Queen's Medical Center with a pathologic diagnosis of acute MI and evaluated the clinicopathologic features of the identified cases. Goldman's classification was used to classify discrepant cases. Results: Of 529 autopsies performed during 2006–2017, 19 (3.6%) demonstrated acute/subacute MI as a pathologic diagnosis. A subset of cases exhibited unremarkable gross findings, with the diagnosis of acute MI rendered by microscopic examination alone (7/19, 36.8%). Thrombosis was identified in a minority of cases (3/19, 15.8%). Major clinical-pathologic discrepancies were identified in four cases (21.1%). Of these, two underwent a specific ischemic event, namely cardiac allograft vasculopathy (CAV) and myocardial infarction with angiographically normal coronary arteries (MINCA). The remaining two cases showed evidence of concurrent sepsis, making the clinical diagnosis of acute MI challenging. Conclusion: Although acute MI is an uncommon diagnosis rendered at hospital autopsy, a notable subset of cases demonstrates diagnostic discrepancy between the clinical impression and ultimate pathologic diagnosis. Interestingly, most cases are not related to atherosclerotic plaque disruption and rather are secondary to increased oxygen demand or decreased supply and thus best classified as a type 2 MI.